Strategi Manajemen Kurikulum Sebagai Upaya Peningkatan Kualitas Pendidikan Keagamaan Di Lembaga Pondok Pesantren - Sofa Luthfiah, Efluida; Lukmanul Hakim, Luki (Manajerial | Journal Manajemen pendidikan islam, 2023)
The purpose of this study was to determine how the curriculum management strategy as an effort to improve the quality of religious education at the Miftahul Huda Al-Faqih Manonjaya Tasikmalaya Islamic Boarding School. This research uses descriptive qualitative research methods with a case study approach through observation, interviews and documentation. Data analysis techniques used include data collection, data reduction, data presentation and conclusion drawing. The results of this study are curriculum management strategies such as curriculum planning at the Miftahul Huda Al-Faqih Manonjaya Tasikmalaya Islamic Boarding School includes activities to determine goals, determine the learning process, and determine learning materials. Its management includes activities of managing learning materials, managing teachers, and managing the time and schedule of teaching and learning activities. In its implementation, it teaches values that will improve the quality of religious education. The education system adheres to a modern semi-salaf system with the yellow book as a reference. The evaluation of its implementation uses test and non-test forms of evaluation and indirectly uses the CIPP evaluation model (context, input, process, and product).